Achieving success and innovation in global sourcing : perspectives and practices : 9th Global Sourcing Workshop 2015 La Thuile, Italy, February 18-21, 2015 revised selected papers - Oshri, Ilan 1953-; Kotlarsky, Julia 1973-; Willcocks, Leslie P. 1951- (Lecture notes in business information processing / series editors Wil van der Aalst [y otros cuatro], 2015)
The book offers a review of the key topics in outsourcing and offshoring, populated with practical frameworks that serve as a tool kit to students and managers. The range of topics covered is wide and diverse, but predominately focused on how to achieve success and innovation in global sourcing. The topics discussed combine theoretical and practical insights regarding challenges that industry leaders, policy makers, and professionals face. Case studies from various organizations, industries and countries are used extensively throughout the book to illustrate results and findings.